Methods of Infantile Colic Correction in the Context of Evidence-Based Medicine - L.O. Rakovska (Zaslavsky O.Yu., 2015)
The article considers the methods of correction of infantile colic, the causes and the mechanism of which still remain poorly understood. Various methods to relieve the symptoms of colic in infants, such as psychotherapy, physical methods of soothing, methods for dietary and pharmacological correction, are analyzed in detail, and an assessment of their effectiveness is provided on the basis of clinical trials being conducted.